Implications of Sensory Processing and Attentional Differences Associated With Autism in Academic Settings: An Integrative Review - Mallory, Courtney; Keehn, Brandon (Frontiers in Psychiatry, 2021)
The impact of classroom environments on student engagement and academic performance is well documented. Autism spectrum disorder (ASD) is associated with atypical sensory processing and attentional impairments, which may lead to challenges in successfully accessing educational material within these settings. These symptoms may help explain why students with ASD show discrepancies between intellectual ability and academic performance. Given the increasing number of students with ASD present in classrooms, understanding strengths and weaknesses in sensory processing and attention is necessary in order to design better classroom environments and develop more efficacious accommodations and interventions to support optimal student success. Therefore, the objectives of this review are to provide a brief review of the current literature on sensory processing and attention in ASD, survey how sensory and attentional functions affect academic outcomes in both neurotypical and ASD learners, and suggest potential accommodations/interventions for students with ASD based on these findings.